Comparison of the 3D-microstructure of human alveolar and fibula bone in microvascular autologous bone transplantation: a synchrotron radiation μ-CT study - Wüster, Jonas; Hesse, Bernhard; Rothweiler, Rene; Bortel, Emely; Gross, Christian; Bakhtiyari, Shima; King, Andrew; Boller, Elodie; Gerber, Javier; Rendenbach, Carsten; Fretwurst, Tobias; Preissner, Saskia; et al. (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: Autologous bone transplantation is successfully used in reconstructive surgery of large/critical-sized bone defects, whereby the microvascular free fibula flap is still regarded as the gold standard regarding the reconstruction of such defects in the head and neck region. Here, we report the morphological and lacunar properties of patient-paired bone samples from eight patients from the jaw (AB; recipient site) and the fibula (FB; donor site) on the micron length-scale using Synchrotron µ-CT. Insights into differences and similarities between these bone structures could offer a better understanding of the underlying mechanism for successful surgical outcomes and might clear the path for optimized, nature-inspired bone scaffold designs. Methods: Spatial vessel-pore arrangements, bone morphology, fluid-simulation derived permeability tensor, osteocyte lacunar density and lacunar morphology are compared. Results: The orientation of the vessel system indicates a homogenous vessel orientation for AB and FB. The average mineral distance to the closest vessel boundary is higher in AB than in FB (the mean is 96 μm for AB vs. 76 μm for FB; p=0.021). Average osteocyte lacunar density is found to be higher in AB than in FB (mean 22,874 mm3 vs. 19,376 mm3 for FB; p= 0.038), which might compensate for the high distance from the mineral to the nearest vessel. No significant differences in lacunar size or shape are found between paired AB and FB. Discussion: A comparable vessel network and similar distribution of vessel porosity between AB and FB may allow the FB graft to exhibit a high regeneration potential when connected to AB, and this might correlate with a high osteoinductive and osteoconductive potential of FB when connected to AB. Since widely used and potent synthetic bone grafts exist, new insight into the bone structure of well-established autologous bone grafts, such as the free fibula flap, could help to improve the performance of such materials and therefore the design of 3D scaffolds.